GENEALOGI METODE SOROGAN (Telisik Historis Metode Pembelajaran dalam tradisi Pesantren) - Abdurrahman (Jurnal Studi Pesantren, 2020)
Pesantren has 5 elements, one of which is the teaching of classic books called the yellow book. The term "book" is always maintained in pesantren to distinguish it from new books. Since the 16th century, there have been translations of these classical books, and starting in the 18th century there were many Archipelago who studied in Arabic; Egypt and Mecca. The pesantren then brought these books along with their curriculum. The preservation of classic dipesantren books is very much influenced by the tradition of sanad or isnad. This research attempts to trace the origin of the methodological genealogy of the sorogan method which is still used in pesantren in Nusantara as one of the methods of learning the yellow book. By using a library research methodology and genealogical analysis, the researcher believes that the genealogical traces of the sorogan method are rooted in 2 methods: (1) the 'aradh method in the tradition of the narration of the hadith, and (2) the tadarus method in the tradition of the narration of the Qur'an' an.